Impact of Artificial Intelligence in Electoral Democracy: Constutional Perspective (Tribhuvan University Law Journal, 2025)
Artificial Intelligence (AI) is one of the fastest growing technologies which has dominated wide aspects of human life, free and fair election and electoral process remains one of its impact areas. AI is increasingly being implemented in voter registration, online campaigning, and vote analysis. One of the major goals of incorporating AI into elections was to ensure voters right to select their representatives by making democratic processes efficient, simple, fair and successful; but, as generative AI has developed, it is more of a challenge to manage fake news, audios videos, texts, and communication and even sometimes electoral fraud, which leads to misrepresentation and election manipulation. Democratic norms and principles indicate that true representation occurs through free, fair, and impartial elections; however, these principles have directly been impacted by AI’s unregulated rapid growth. Nepal has also witnessed the shallow effect of these AI tools through social media in the 2022 election. Misinformation, manipulation, widespread fake news, text and videos in the form of social media contents were some of the approaches misused by tech savvy political parties to win public favor, in which they became successful. This reflects, there is a good potential that anyone, internal or external, domestic or international, with technical knowledge in his will, can create significant interference in Nepal’s election, even though the growing impact of AI in Nepal is not as profound as it is in other developed countries. Moreover, the absence of adequate rules governing AI and cybercrime can be seen as major problems that could have an impact on Nepal’s electoral process in upcoming years. Therefore, it is past due for a nation like Nepal to take the expanding role of artificial intelligence and online platforms in elections seriously. To safeguard the fundamental tenet of democracy, appropriate regulations must be formulated, and the people must be educated about these issues through training and awareness efforts.